2001
DOI: 10.1128/iai.69.8.5182-5185.2001
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Upregulation of Urokinase Plasminogen Activator Receptor and CD11b during Tuberculosis and Experimental Endotoxemia

Abstract: Patients with tuberculosis had higher expression of monocyte urokinase receptor (uPAR) and CD11b than controls. In vitro, lipoarabinomannan and lipopolysaccharide (LPS) from Escherichia coli shared the ability to enhance uPAR and CD11b expression on monocytes and granulocytes. In healthy volunteers, LPS induced increases in monocyte and granulocyte uPAR and CD11b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
22
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 14 publications
(8 reference statements)
4
22
0
1
Order By: Relevance
“…By doing so we were able to demonstrate increased expression of uPAR on both monocytes and granulocytes at the primary place of infection. These data are in accordance with previous data showing an increased release of uPAR in both plasma and urine of patients with urosepsis (36) and increased uPAR cell surface expression on monocytes of healthy volunteers injected with endotoxin (9,10).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…By doing so we were able to demonstrate increased expression of uPAR on both monocytes and granulocytes at the primary place of infection. These data are in accordance with previous data showing an increased release of uPAR in both plasma and urine of patients with urosepsis (36) and increased uPAR cell surface expression on monocytes of healthy volunteers injected with endotoxin (9,10).…”
Section: Discussionsupporting
confidence: 93%
“…In humans, i.v. injection of LPS was associated with an upregulation of uPAR on circulating monocytes and granulocytes (9,10). However, the precise role of uPAR in human sepsis is still largely undefined.…”
mentioning
confidence: 99%
“…Human endotoxemia has been used previously by other investigators as an experimental model to examine diverse aspects of the inflammatory response including changes in leukocyte antigen expression. [28][29][30] In the present study, we show that changes in nCD64 expression following LPS administration can generally be characterized as biphasic. In examining relationships between hematological changes and nCD64 expression, we found that LPS administration was accompanied by an initial rapid decline in the absolute neutrophil (ANC) and immature granulocyte counts at 1 h, followed by an Fig.…”
Section: Discussionmentioning
confidence: 88%
“…[28][29][30][50][51][52] Phagocytosis and clearance of apoptotic cells are critical to the resolution of inflammation. 1,2 Integrins, especially the integrin ␣ V ␤ 3, are major receptors for PtdSer and play a major role in the clearance of apoptotic cells.…”
mentioning
confidence: 99%